P‐22: High Performance a‐IGZO TFT Backplanes with Cu Gate and Source/Drain Electrodes for AMOLED Displays. Issue 1 (June 2015) - Zhu, Xiaming; Jiang, Chunsheng; Yuan, Guangcai; Liu, Wei; Li, Xuyuan; Xin, Longbao; Wang, Meili; Wang, Gang
Abstract : We have developed the fabrication processes for bottom gate and etch stopper‐type a‐IGZO TFT with Cu gate and source/drain electrodes. After optimizing the multi‐layer stack structure of the gate insulator, the deposition processes for the gate insulator, a‐ IGZO and etch stopper layers, and tuning the post‐annealing treatments, the TFT performance and stability of the a‐IGZO backplanes were improved evidently. In this report, we discussed the improvements in TFT performance uniformity and reliability for the a‐IGZO TFT backplanes with Cu gate and source/drain electrodes by optimizing the fabrication processes. Finally, 14‐ inch qHD and 55‐inch ultra high‐definition AMOLED panels driven by the high performance and stable a‐IGZO TFT backplanes with Cu electrodes were successfully developed.